Unions, Industrial Relations and Market Income Inequality in Canada’s Provinces - Scrimger, Phillippe (Relations industrielles / Industrial Relations, 2020)
While decades of scholarship point to the broad consensus that unions compress the distribution of wages and incomes, recent empirical contributions suggest that unions’ within-country egalitarian effect is dwindling, as unions decline and membership composition changes. What is more, unions now operate in an increasingly difficult political economy transformed by, among other forces, globalization, financialization and fiscal austerity. At the same time, there is an increased demand for unions to play a broader role in a movement for distributive justice.Transposing these debates to the Canadian provincial context, this article asks whether unions still matter for reducing inequality. Considering the role of industrial relations more broadly by taking into account strike activity and collective labour statutes, the article explores the relationship between union power and market income inequality over a period ranging from 1984 to 2012. This empirical contribution is framed in theories from comparative capitalism, economics, and sociology.Descriptive longitudinal statistics support the well-documented union decline narrative. On average, union density and strike activity have declined in the provinces. As for the quality of collective labour rights, it is argued that the relative apparent stability of statutes conceals more substantive issues with Wagnerism as an organizing model. Linking unions to inequality, results from multivariate regressions using panel data suggest that union power still matters for limiting market income inequality. While estimates for strike action are not statistically significant, those for union density and the quality of collective labour statutes suggest that unions still exert an inequality-reducing effect. However, the rarity of significant estimates across models using different measures of inequality indicates that this effect is by no means comprehensive.